Analysis of Student’s Mathematical Literacy Ability on Linear Program Material Reviewed From Cognitive Styles - Harischa Isrothul Jannah; Vera Dewi Susanti; Edy Suprapto (AL-ISHLAH: Jurnal Pendidikan, 2023)
The low mathematical literacy is influenced by internal student factors. One that influences is the cognitive style of students. This study aims to describe students' mathematical literacy abilities with field-independent (FI) and field-dependent (FD) cognitive styles on linear program materials.  This research is qualitative.  The subjects of this study were class X MM PKM students of SMK Cendekia Madiun for the 2021/2022 Academic Year, as 16 students. The data were analyzed descriptively.  To group students using GEFT questionnaires and data collection techniques using a test for describing mathematical literacy skills and using interviews.   The result of this study is that students with a Field Independent (FI) cognitive style master the following aspects of literacy ability:  communication skills, mathematical abilities, representation abilities, reasoning and argument skills, problem-solving strategy skills, ability to use language and symbol operations, formal and technical.  Meanwhile, students with a Field Dependent (FD) cognitive style master the following aspects of literacy: communication skills, mathematical skills, representation abilities, problem-solving strategy skills, ability to use language and symbol operations, formal and technical. This research is limited only by 2 students. In the future, it is necessary to conduct research involving more students with different materials.